2021
DOI: 10.1155/2021/4731349
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing mRNAsi-Related Genes Identifies Novel Prognostic Markers and Potential Drug Combination for Patients with Basal Breast Cancer

Abstract: Basal breast cancer subtype is the worst prognosis subtypes among all breast cancer subtypes. Recently, a new tumor stemness index-mRNAsi is found to be able to measure the degree of oncogenic differentiation of tissues. The mRNAsi involved in a variety of cancer processes is derived from the innovative application of one-class logistic regression (OCLR) machine learning algorithm to the whole genome expression of various stem cells and tumor cells. However, it is largely unknown about mRNAsi in basal breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…Studies have suggested that mRNAsi might serve as an effective index for the survival, classification, and disease progression of tumor patients [25][26][27]. Huang et al found that basal breast cancer patients have high mRNAsi values [28]. In the present study, we found that the mRNAsi value in LUAD samples was higher than that in normal samples, and survival analysis revealed that patients in the high mRNAsi group had a poor prognosis.…”
Section: Discussionsupporting
confidence: 54%
“…Studies have suggested that mRNAsi might serve as an effective index for the survival, classification, and disease progression of tumor patients [25][26][27]. Huang et al found that basal breast cancer patients have high mRNAsi values [28]. In the present study, we found that the mRNAsi value in LUAD samples was higher than that in normal samples, and survival analysis revealed that patients in the high mRNAsi group had a poor prognosis.…”
Section: Discussionsupporting
confidence: 54%
“…We also calculated the mRNAsi for HCC samples obtained from five cohorts. A higher mRNAsi represents a lower level of differentiation of a sample ( 20 ). Survival analysis was performed only using samples obtained from patients for whom the survival duration was less than 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…There is still an urgent need for reliable and robust markers that can be used for predicting the prognosis of different HCC cohorts and the effect of drug therapy, which are also of great value for the precise treatment of patients. Several studies have shown that the stemness index is effective for the prediction of prognosis and drug resistance in multiple malignancies (20)(21)(22)(23). Here, we aimed to explore the regulatory mechanism under sorafenib-resistant conditions using the stemness index.…”
Section: Introductionmentioning
confidence: 99%
“…RAD51AP1 is also significantly up-regulated in triple negative breast cancer and its overexpression is associated with poor outcome, suggestive of prognostic value in this malignancy [33]. More recently, RAD51AP1 was one of four other genes (EXO1, TRIM59 and SEPT3) that can be an independent protective prognostic factor in patients with basal breast cancer [34]. Apart from its prognostic value, the siRNA data also points towards an interesting therapeutic target.…”
Section: Discussionmentioning
confidence: 99%